Language Technology Initiative: digital competence enhancement case study - Zigrīda Vinčela; Jana Kuzmina (Baltic Journal of English Language, Literature and Culture)
The advancement of artificial intelligence and other related automation technologies has put forward new challenges at the tertiary education level, namely, the development of digital competence alongside the development of core knowledge, skills and competence of the study programme. These preconditions create favourable environments and justify the need to elaborate on digital competences in the humanities. To address these needs, the course Introduction to Applied Linguistics and Language Technologies has been designed as a part of the EU Recovery and Resiliency Facility project Language Technology Initiative and included in the BA study programme. The course comprises activities specifically targeted at the skills for language technology application for automated text analysis and synthesis and audiovisual material processing in students’ professional activity and research. The goal of the present study was to uncover which digital competence areas are enhanced, what competence levels are reached by these activities according to the definitions in the DigComp 2.2 framework and pilot them. To reach the goal, the present exploratory case study focused on an in-depth investigation of the mentioned course, i.e., eight activities that aim at language technology skills were mapped according to DigComp 2.2 and piloted. This process revealed that the activities cover two competence areas at level 6 and level 7. The piloting results were summarised through the course performance metrics and the corpus analysis of students’ questionnaires.